Bakwet refugees in their own land - Guy, Malcolm; Productions Multi Monde (New York Cinema Guild, 1989)
Takes a look ar the human rights situation in the Philippines, examines the underlying causes of forced evacuation of thousands of Filpino peasants from their homes, and cosiders possible solutions to the present situation.
Photographer, Romulo Regalado; editor, Ren Riberge; narrator, Malcolm Guy; music, Richard Angers, Ronnie Quesada.
Keywords: Human rights -- Philippines; Forced migration -- Philippines; Peasantry -- Philippines; Philippines -- Sociak conditions